Impact of electroviscous effect on viscosity in developing highly concentrated protein formulations: Lessons from non-protein charged colloids - Jinjiang Li; Yuan Cheng; Xiaodong Chen; Songyan Zheng (Elsevier, 2019)
Subcutaneous delivery of highly concentrated protein formulations is paramount for reducing healthcare cost and improving patient compliance, where reducing the solution viscosity of formulations is critical for drug delivery. The objective of this paper is to provide some mechanistic understanding about the contribution of electrostatic repulsion to the viscosity of protein solutions at high concentrations, along with the effect of excipients such as salts on relative viscosity. Proteins are treated as charged colloids in this paper. At high concentrations, the electrical double layer starts to overlap, and secondary electroviscous effect becomes significant in addition to primary electroviscous effect. In other words, the hydrodynamic volume of proteins plays a great role in influencing their solution viscosity because of the excluded volume effect. Currently, it is hypothesized that the high viscosity of concentrated protein solutions is attributed to formation of clusters due to either electrostatic attraction or hydrophobic interactions, especially for monoclonal antibodies, in which anybody molecules in high concentration formulations may form networks. Consequently, viscosity reduction in the presence of inorganic or organic salts in these formulations is due to breaking up of these networks. In this review, authors hope to provide another point of view based on the effect of the electrostatic repulsion on the excluded volume-hydrodynamic volume. Finally, authors hope the proposed theoretical framework can be used to guide excipient selection in the product development of highly concentrated proteins. Keywords: Protein formulations, Viscosity, Electroviscous effect, Drug delivery, High concentration, Subcutaneous injection, Electrostatic interaction